The development of human embryo in the Quran, Surah al- Mu’minun (23): 12-14. - Deuraseh, Nurdeng; Yaakub, Noor Inayah (EuroJournals Publishing, Inc., 2010)
This article highlights different stages of formation of the human embryo along with the description of every stage of the embryonic development as mentioned in the Quran, Surah al-Mu’minun. This study shows that God creates a child in a mother’s womb and brings about the child chronological evolution to full life, while the parents only play an instrumental role in this creative process. The Quran says: We have created man out of an extraction of clay (the origin of semen). Then we turn it into semen and settle it in a firm receptacle. We then turn semen into a clot (‘alaqah) (literally, something hanging, that is, from the womb) which we then transmute into a lum (mudghah). We then create bones which we clothe with flesh. Then, we transmute it into a new mode (of ensoulment)-blessed be then Allah, the best of creators. (Al-Quran, Surah (Chapter) Al-Mu’minun (23): 12-14, see also Al-Hajj (22): 5).